Paleogeography of the upper Paleozoic basins of southern South America: An overview - Limarino, Carlos Oscar (2006)
The paleogeographic evolution of Late Paleozoic basins located in southern South America is addressed. Three major types of basins are recognized: infracratonic or intraplate, arc-related, and retroarc. Intraplate basins (i.e., Paraná, Chaco-Paraná, Sauce Grande-Colorado, and La Golondrina) are floored by continental or quasi-continental crust, with low or moderate subsidence rates and limited magmatic and tectonic activity. Arc-related basins (northern and central Chile, Navidad-Arizaro, Río Blanco, and Calingasta-Uspallata basins and depocenters along Chilean Patagonia) show a very complex tectonic history, widespread magmatic activity, high subsidence rates, and in some cases metamorphism of Late Paleozoic sediments. An intermediate situation corresponds to the retroarc basins (eastern Madre de Dios, Tarija, Paganzo, and Tepuel-Genoa), which lack extensive magmatism and metamorphism but in which coeval tectonism and sedimentation rates were likely more important than those in the intraplate region. According to the stratigraphic distribution of Late Paleozoic sediments, regional-scale discontinuities, and sedimentation pattern changes, five major paleogeographic stages are proposed. The lowermost is restricted to the proto-Pacific and retroarc basins, corresponds to the Mississippian (stage 1), and is characterized by shallow marine and transitional siliciclastic sediments. During stage 2 (Early Pennsylvanian), glacial-postglacial sequences dominated the infracratonic (or intraplate) and retroarc basins, and terrigenous shallow marine sediments prevailed in arc-related basins. Stage 3 (Late Pennsylvanian-Early Cisuralian) shows the maximum extension of glacial-postglacial sediments in the Paraná and Sauce Grande-Colorado basins (intraplate region), whereas fluvial deposits interfingering with thin intervals of shallow marine sediments prevailed in the retroarc basins. To the west, arc-related basins were dominated by coastal to deep marine conditions (including turbiditic successions). In the Late Cisuralian (stage 4), important differences in sedimentation patterns are registered for the western arc-related basins and eastern intraplate basins. The former were locally dominated by volcaniclastic sediments or marine deposits, and the intraplate basins are characterized by shallow marine conditions punctuated by several episodes of deltaic progradation. Finally, in the Late Permian (stage 5), volcanism and volcaniclastic sedimentation dominated in basins located along the western South American margin. The intraplate basins in turn were characterized by T-R cycles composed of shallow marine, deltaic, and fluvial siliciclastic deposits. © 2006 Elsevier Ltd. All rights reserved.